Polski sukces sukcesu w świetle opracowań leksykograficznych i literatury popularnopsychologicznej - Katarzyna Skowronek (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2017)
In her article the author discusses “success” – one of most important words defining the contemporary culture and people. She asks about the meaning of the word and compares its use in self-help books with the definition found in dictionaries of the Polish language. How is the contemporary “culture of success” created by those “new” meaning profiles? The first part of the analysis concerns the semantics of “success” in selected historical and modern dictionaries. K. Skowronek points out that the word has undergone the process of amelioration: from a neutral element to a positive one. The second part of the article is a narrative analysis. The author presents the semantics of the word in contemporary self-help books. She highlights its individualistic and self-disciplining character. Nowadays, success is synonymous with happiness and the meaning of life. It predominantly entails an obsessive chase while not necessarily a real achievement.